The role of the government in the process of appointment of honorary and contract workers in Pasaman Regency - Riska Dwi Cahyani; Sinta Westika Putri (Priviet Social Sciences Journal, 2025)
This study aims to analyze the role of the government in the process of appointing honorary and contract workers in Pasaman Regency and the factors that influence the role of the government in the process of appointing honorary and contract workers in Pasaman Regency. The appointment of contract workers to PPPK is the process of changing the status of contract employees to that of Government Employees with Work Agreements, who are appointed based on work agreements for a certain period to carry out government duties. This process is an effort by the government to provide a more certain status and equal rights to contract employees who have not had a clear status as PPPK or ASN. This study used a qualitative method with a descriptive approach and data collection techniques in the form of interviews and documentation. This study uses Rasyid's theory (1997) which states that there are 4 roles of government consisting of (1) Role as Regulator, (2) Role as Dynamicator, (3) Role as Facilitator and (4) Role as Catalyst. The results of the study show that the Pasaman Regency Government has carried out these four roles, but has not been running optimally. As a regulator, the regional government acts only plays a role as an implementer of central policies without the authority to establish new regulations. As a dynamicator, the government is trying to mobilize regional apparatuses and honorary workers to actively participate in PPPK selection, although coordination is not yet optimal. As a facilitator, BKPSDM provides consultation services, administrative assistance, and digital-based information access but is still hampered by human resources. Meanwhile, as a catalyst, the government plays a role in accelerating the administrative process and encouraging the resolution of obstacles between the agencies. Bureaucratic structure, communication, resources, and disposition are factors that affect the implementation of policies.  The primary challenges are inadequate discipline, heavy workload, shortage of digital system expertise, and small workforce.  To make the process of selecting contract and honorary employees more efficient and transparent, this study suggests enhancing agency collaboration, bolstering human resource capabilities, and streamlining bureaucratic structures.